The influence of the quality of services and facilities on the satisfaction of domestic tourists at Plumeria Ecopark Muara Enim Regency - Daniel Sihombing (Trigin Publisher, 2023)
Plumeria Ecopark is an educational tourist spot that is perfect for families. A spacious place that provides playgrounds for children with the theme of local wisdom. This study aims to see whether the quality of services and facilities provided by Plumeria Ecopark have provided satisfaction to tourists. The method used in this research is quantitative by distributing questionnaires to 100 visiting local tourists. The method used in this study is quantitative where the results of the answers are measured by the Likert scale. With the help of SPSS in terms of data processing, this study obtained the results that service quality did not affect visitor satisfaction with the results of service quality (X1) as much as 1.090 less than t table 1.984 (1.090 <1.984) or the sig.t value for the facility variable was 0.278 greater of 0.05 (0.278<0.05). While facilities have an effect on tourist satisfaction with the results of facilities (X2) as much as 4.667 greater than t table 1.984 (4.667 > 1.984), or the sig.t value for the service quality variable is 0.000 less than 0.05 (0.000 <0.05). Simultaneously the quality of services and facilities affect tourist satisfaction. The more improved the quality of services and facilities, the more satisfied tourists will be.